Economic Openness and Growth in China and India: A Comparative Study - Yin, Fengbao; Hamori, Shigeyuki (Journal of Reviews on Global Economics, 2012)
Abstract: This paper examines the Melo-Vogt hypotheses and compares the effects of economic openness in China and India. The two defining characteristics of this paper are the addition of a cross term containing the economic globalization index to the traditional import demand function model, and testing for cointegration between variables using Hansen's (1992) method that considers structural change. The results indicate that increasing economic openness has had a greater impact on the economy in China than in India.